Controlling depth of electrosurgery after curettage of skin tumors—an in vitro study. (18th September 2019) - Taheri, Arash; Green, Courtney; Mansoori, Parisa
Abstract: Background: Depth of tissue injury in electrosurgery depends on generator power, electrode size, speed of electrode movement on tissue, and current delivery method. We sought to evaluate the depth of tissue injury associated with different methods of electrocoagulation in an effort to make electrocoagulation more reproducible. Methods: A knife‐shaped electrode was used to apply an electrosurgical current to the surface of a piece of bovine liver. Different electrosurgical methods were performed. Cross sections of the liver were then studied for tissue effect. Results: Fulguration provided only superficial coagulation. Contact electrocoagulation and electrodesiccation using the flat side of the electrode provided significantly deeper levels of coagulation and were associated with less smoke than fulguration. Desiccation provided the deepest tissue effect. Conclusions: Electrofulguration can be used for superficial tissue destruction. For deeper coagulation, a relatively larger electrode can be used in contact mode. Slower movement of the electrode on tissue in contact mode is associated with desiccation and the deepest level of tissue destruction.